Preparation of superabsorbent resin with fast water absorption rate based on hydroxymethyl cellulose sodium and its application. (1st December 2019) - Cheng, Sha; Liu, Xiaomei; Zhen, Jianghong; Lei, Ziqiang
Highlights: Hydroxymethyl cellulose sodium is a new cellulose derivative to prepare SAR. The water absorption rate reached equilibrium at 15 min in distilled water. The water retention of SAR at different temperatures was measured and its was good. The evaporation rate is 9.49% lower than neat soil when the content of SAR is 0.10%. Abstract: To study the application of superabsorbent resin (SAR) in preventing water evaporation in soil, hydroxymethyl cellulose sodium-g-poly (acrylic acid-co-2- acrylamido-2-methyl-1-propanesulfonic acid)/laterite (NaHMC-g-P (AA-co-AMPS)/ laterite) was prepared by radical polymerization. The structure and morphology of SAR were characterized by FTIR, SEM and TGA. The factors affecting the water absorbency of SAR were studied and the water absorption of the resin under the optimum synthetic conditions reached the equilibrium at 15 min in distilled water, and the optimum water absorption of SAR was 1329 g/g, 269 g/g and 140 g/g in distilled water, tap water and 0.9 wt% NaCl solution, respectively. The swelling kinetic mechanism of the SAR was explained by the pseudo-second-order swelling kinetics model and Ritger-Peppas model. The effects of soil type, particle size and content of SAR on water evaporation rate in soil were studied.